2020
DOI: 10.3389/fnagi.2020.00117
|View full text |Cite
|
Sign up to set email alerts
|

Older Age Increases the Amplitude of Muscle Stretch-Induced Cortical Beta-Band Suppression But Does not Affect Rebound Strength

Abstract: Healthy aging is associated with deterioration of the sensorimotor system, which impairs balance and somatosensation. However, the exact age-related changes in the cortical processing of sensorimotor integration are unclear. This study investigated primary sensorimotor cortex (SM1) oscillations in the 15-30 Hz beta band at rest and following (involuntary) rapid stretches to the triceps surae muscles (i.e., proprioceptive stimulation) of young and older adults. A custom-built, magnetoencephalography (MEG)-compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
2
15
1
Order By: Relevance
“…COP peak displacements, times to peak displacement, and recovery displacement showed comparable results with the group of young adults in that study. Moreover, the peak displacements observed in the current study were in line with the study by Walker et al (2020) which utilized a protocol closely resembling the one used here in the fast condition. The finding suggests treadmill-based perturbed postural balance assessment has good concurrent validity compared with the test performed using a purpose-built device consisting of a commercial force plate driven by electromechanical cylinders.…”
Section: Comparison With Previous Studies Utilizing Purpose-built Devicessupporting
confidence: 89%
“…COP peak displacements, times to peak displacement, and recovery displacement showed comparable results with the group of young adults in that study. Moreover, the peak displacements observed in the current study were in line with the study by Walker et al (2020) which utilized a protocol closely resembling the one used here in the fast condition. The finding suggests treadmill-based perturbed postural balance assessment has good concurrent validity compared with the test performed using a purpose-built device consisting of a commercial force plate driven by electromechanical cylinders.…”
Section: Comparison With Previous Studies Utilizing Purpose-built Devicessupporting
confidence: 89%
“…Smith et al (2012) demonstrated that PD patients exhibit greater beta ERD after a cue, but prior to a predictable small-magnitude perturbation, compared to healthy control participants in the Cz electrode. Similarly, in the lower extremities study during sitting, Walker et al (2020) reported that beta ERD and ERS appear after the stimulation to rotate the ankle, where the beta ERD was enhanced in the elderly, compared to young people. In addition, some studies showed that brief mechanical perturbations applied by pulling the body during standing posture induced beta ERD after the theta and alpha ERSs with short latencies (Peterson and Ferris, 2018).…”
Section: Introductionmentioning
confidence: 81%
“…This is especially important, since the beta rhythm rebound has been proposed to be a biomarker reflecting functional recovery of the SMI cortex after acute stroke, whereas no clear association between suppression and motor recovery has been found ( 11 , 32 , 33 ). The beta power and the strength of beta modulation have been shown to increase in relation to aging ( 6 , 47 ). However, such changes seem not to occur within a 1-year follow-up period, at least in relatively young adult participants.…”
Section: Discussionmentioning
confidence: 99%
“…In children, the beta power has shown to be reduced than in adults ( 61 ). Concomitantly, several studies have shown that in elderly subjects the beta power at rest is increased than in younger subjects, leading to an increase of beta suppression ( 6 , 47 , 57 , 62 , 63 ), with the exception of Alzheimer’s disease, where the resting-state beta power has been shown to decrease ( 64 ). The frequency of the beta rhythm has also been shown to be lower with increasing age ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation